THE RELATIONSHIP BETWEEN EATING PATTERNS AND NUTRITIONAL STATUS OF GRADE 5-6 STUDENTS OF SDN TANJUNGREJO 1, MALANG CITY - Talitha Sefiuma Khoirin; Apriyani Puji; Juliati Koesrini (Jurnal Ilmiah Keperawatan, 2026)
Nutrition is a major problem among school-aged children, because children who lack nutrition can experience sleepiness and low enthusiasm, which disrupts the learning process at school and will affect concentration and academic performance due to suboptimal brain development. The type of research used is quantitative with a cross-sectional design. The sample consisted of 52 elementary school students. The dependent variable is Nutritional Status, and the independent variable is eating patterns. The study results show that most respondents had good eating patterns, with 46 respondents (88%) at SDN 1 Tanjungrejo , Malang City, and most respondents had good nutritional status, with 43 respondents (83%) at SDN 1 Tanjungrejo , Malang City. The Spearman test results showed a p-value of 0.035 < (α = 0.05), indicating a significant relationship between eating patterns and students' nutritional status. The correlation coefficient value r = −0.293 indicates a weak relationship with a negative direction due to category coding. However, conceptually, a good diet still supports better nutritional status.